Case report: Transvenous coil embolization of a high-grade Galenic dural arteriovenous fistula - Cornea, Christiana M.; Quig, Nathan; Yap, Edward; Solander, Sten Y. (Frontiers in Neurology, 2023)
Introduction Galenic dural arteriovenous fistulas (dAVFs) are a rare form of dAVF and rarely described in the literature. Their distinct location requires different surgical approaches than dAVFs occurring at the nearby sites of the straight sinus and torcular Herophili, and their high risk of hemorrhage makes these dAVFs very challenging to approach surgically. In this report, we present a unique case of Galenic dAVF. Case description The patient is a 54-year-old female who presented with a 2-year history of progressive headaches, cognitive decline, and papilledema. A cerebral angiogram demonstrated a complex dAVF to the vein of Galen (VoG). She underwent transarterial embolization with Onyx-18 which resulted in minimal reduction in arterial venous shunting. She subsequently underwent a successful transvenous coil embolization resulting in complete occlusion of dAVF. The patient’s postoperative course was complicated by interventricular hemorrhage; however, she had a remarkable clinical recovery with resolution of headaches and improvement in cognitive function. A follow-up angiogram completed 6 months post-embolization demonstrated very mild residual shunting. Conclusion In the unique case presented here, we demonstrate the efficacy of transvenous embolization via an occluded straight sinus as an alternative therapeutic option to eliminate cortical venous reflux.